Development of an In Vitro Permeation Test Framework For Naloxone Hydrochloride Intranasal Spray: Establishing IVIVR for Bioequivalence Assessment - Tasmin Ara Sultana; Manar Al-Ghabeish; Steven Chopski; Ross Walenga; Diaa Shakleya; Bryan Newman; Muhammad Ashraf; Ahmed Zidan (Pharmaceutical Research, 2026)

Regional Nasal Drug Deposition in Pediatric vs. Adult Models: In vitro Insights into User Technique and Breathing Patterns Sensitivity - Mohammad Hejazi; Xiomara Owen; David J. Edwards; Michael Hindle; Worth Longest; Theodore Schuman; Ross Walenga; Steven Chopski; Anubhav Kaviratna; Bryan Newman; Laleh Golshahi (Pharmaceutical Research, 2026)
Purpose Although in vitro studies recommended for establishing bioequivalence of locally acting nasal suspension products provide useful information regarding product performance, currently they are not designed to fully account for variability introduced by patient-specific factors such as administration technique and breathing patterns. This limitation, combined with ethical and practical challenges in conducting pediatric clinical trials, creates a knowledge gap in understanding age-related differences in nasal drug delivery. Methods Anatomically realistic in vitro nasal models representing an average child and adult, in terms of total drug delivery to the sites of intended action posterior to nasal valve, were used to investigate the sensitivity of regional nasal drug deposition to variations in administration parameters and breathing conditions. Three breathing conditions were evaluated: breath hold, gentle sniffing, and vigorous sniffing. Administration parameters were varied using a Box-Behnken experimental design. Results Results showed that for commercially available nasal sprays, breathing patterns did not significantly affect drug delivery in the adult model, but extreme conditions (no breathing vs. vigorous sniffing) caused significant differences in anterior deposition in the child model. Differences between gentle sniffing and the other conditions were not statistically significant. The sensitivity analysis revealed that in vitro drug deposition patterns differ between child and adult nasal cavities under identical user parameter variations, and variable importance differed across nasal cavity regions. Conclusions This study demonstrates the potential for targeted drug delivery by enabling the identification of the optimal administration parameters to achieve desired outcomes, such as enhanced drug deposition in specific nasal regions.

Using Lung Regional Deposition Modeling as Model-Integrated Evidence for Locally Acting Orally Inhaled Drug Products - Ross L. Walenga; Steven G. Chopski; Jae H. Lee; Fenggong Wang; Meng Hu; Andrew H. Babiskin; Lanyan Fang; Liang Zhao (Pharmaceutical Research, 2025)

Numerical, Hydraulic, and Hemolytic Evaluation of an Intravascular Axial Flow Blood Pump to Mechanically Support Fontan Patients - Amy L. Throckmorton; Jugal Y. Kapadia; Steven G. Chopski; Sonya S. Bhavsar; William B. Moskowitz; Scott D. Gullquist; James J. Gangemi; Christopher M. Haggerty; Ajit P. Yoganathan (Annals of Biomedical Engineering, 2011)